Barriers and Facilitators to Safe Food Handling among Consumers: A Systematic Review and Thematic Synthesis of Qualitative Research Studies. - Ian Young; Lisa Waddell (PLoS ONE, 2016)
Foodborne illness has a substantial health and economic burden on society, and most cases are believed to be due to unsafe food handling practices at home. Several qualitative research studies have been conducted to investigate consumers' perspectives, opinions, and experiences with safe food handling at home, and these studies provide insights into the underlying barriers and facilitators affecting their safe food handling behaviours. We conducted a systematic review of previously published qualitative studies in this area to synthesize the main across-study themes and to develop recommendations for future consumer interventions and research. The review was conducted using the following steps: comprehensive search strategy; relevance screening of abstracts; relevance confirmation of articles; study quality assessment; thematic synthesis of the results; and quality-of-evidence assessment. A total of 39 relevant articles reporting on 37 unique qualitative studies were identified. Twenty-one barriers and 10 facilitators to safe food handling were identified, grouped across six descriptive themes: confidence and perceived risk; knowledge-behaviour gap; habits and heuristics; practical and lifestyle constraints; food preferences; and societal and social influences. Our overall confidence that each barrier and facilitator represents the phenomenon of interest was rated as high (n = 11), moderate (11), and low (9). Overarching analytical themes included: 1) safe food handling behaviours occur as part of a complex interaction of everyday consumer practices and habituation; 2) most consumers are not concerned about food safety and are generally not motivated to change their behaviours based on new knowledge about food safety risks; and 3) consumers are amenable to changing their safe food handling habits through relevant social pressures. Key implications and recommendations for research, policy and practice are discussed.